Preferensi Wisatawan Terhadap Tempat Rekreasi Pantai Air Manis di Kota Padang dengan Menggunakan Analisis Konjoin - Julian Heru Saputra; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Tourism sector is one sector that can be developed so that can bring benefits to the surrounding area. The development of tourism has economic impact as expanding businesses and opportunities for employment. One of the attractions in West Sumatra is Air Manis Beach. The purpose of this research is to find out how the combination of attribute from the level of visitor preferences with Air Manis Beach. The type of research used is survey research. Population in this research was visitors Air Manis Beach and used sample as much 100 visitors. The sampling is accidental sampling method. Instrument in this research is questionnaire. Data analysis used is conjoint analysis. Research result from the most popular combination of visitors is beach, amiable and attractive, and mosque. Combinations that less liked by visitors are food and beverages, broadminded and ATV(All Terrain Vehicle).Keywords–Conjoint Analysis, Attributes, Preferences, Tourism.